Neuroprotective Effects of Salidroside in the MPTP Mouse Model of Parkinson’s Disease: Involvement of the PI3K/Akt/GSK3β Pathway - Wei Zhang; Hong He; Hujie Song; Junjie Zhao; Tao Li; Leitao Wu; Xiaojun Zhang; Jianzong Chen (Parkinson's Disease)
The degenerative loss through apoptosis of dopaminergic neurons in the substantia nigra pars compacta plays a primary role in the progression of Parkinson’s disease (PD). Our in vitro experiments suggested that salidroside (Sal) could protect against 1-methyl-4-phenylpyridine-induced cell apoptosis in part by regulating the PI3K/Akt/GSK3β pathway. The current study aims to increase our understanding of the protective mechanisms of Sal in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropypridine- (MPTP-) induced PD mouse model. We found that pretreatment with Sal could protect against MPTP-induced increase of the time of turning downwards and climbing down to the floor. Sal also prevented MPTP-induced decrease of locomotion frequency and the increase of the immobile time. Sal provided a protection of in MPTP-induced loss of tyrosine hydroxylase-positive neurons in SNpc and the level of DA, DOPAC, and HVA in the striatum. Furthermore, Sal could increase the phosphorylation level of Akt and GSK3β, upregulate the ratio of Bcl-2/Bax, and inhibit the activation of caspase-3, caspase-6, and caspase-9. These results show that Sal prevents the loss of dopaminergic neurons and the PI3K/Akt/GSK3β pathway signaling pathway may have mediated the protection of Sal against MPTP, suggesting that Sal may be a potential candidate in neuroprotective treatment for PD.